Peningkatan Pemberdayaan Perempuan Melalui Usaha Pangan Agribisnis Berbasis Green Entrepreneurship - Indrajit Wicaksana; Milliyantri Elvandari; Rika Yayu Agustini (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The women’s group in Pasirukem Village has established a food production business but still faces challenges in production and business management, as well as a lack of understanding of the green economy. Based on these issues, this program aims to enhance the empowerment of women entrepreneurs in Pasirukem Village through green entrepreneurship by improving production and business management aspects. The program seeks to increase the knowledge and skills of participants to develop sustainable green entrepreneurship-based businesses. Activities include socialization and training on green entrepreneurship, food nutrition content, and waste management, supported by technology transfer in the form of organic and non-organic waste processing machines and a food dehydrator. The outcomes of this program show improved knowledge of green entrepreneurship among participants. The availability of production and waste processing machines is expected to enhance the capabilities of the women’s group in Pasirukem Village and provide solutions for advancing women’s empowerment.